2014
DOI: 10.1503/cjs.023013
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of the Alvarado score in predicting acute appendicitis in the black South African population needs to be validated

Abstract: E121 RESEARCH • RECHERCHEThe accuracy of the Alvarado score in predicting acute appendicitis in the black South African population needs to be validated Background: The Alvarado score is the most widely used clinical prediction tool to facilitate decision-making in patients with acute appendicitis, but it has not been validated in the black South African population, which has much wider differential diagnosis than developed world populations. We investigated the applicability of this score to our local populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 20 publications
5
24
2
Order By: Relevance
“…8 Other studies failed to prove the benefit of AS in ruling out AA and suggested that ethnic difference may account for this. 9,10 Our results were in concordance with a similar study performed on similar population in the Middle East.…”
Section: Discussionsupporting
confidence: 92%
“…8 Other studies failed to prove the benefit of AS in ruling out AA and suggested that ethnic difference may account for this. 9,10 Our results were in concordance with a similar study performed on similar population in the Middle East.…”
Section: Discussionsupporting
confidence: 92%
“…18 The classic textbook presentation is relatively uncommon. Although sophisticated imaging technology has allowed early diagnosis in many centres in the developed world, this is often not available in the developing world.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with aappendicitis in South Africa have increased rates of perforation and poorer outcomes (22). Reduced access to advanced imaging techniques, and inability of power prognostic clinical decision making tools (Alvarado score) to aid clinicians at primary care facilities, in addition to the patient behavior patterns and environment are all factors contributing to this increased anatomic severity (23). …”
Section: Discussionmentioning
confidence: 99%
“…This is important as the lack of a uniform system of classifying severity has made it difficult to provide universal evidence based recommendations for acute appendicitis. Previous scoring systems, such as the Alvarado score, are only utilized for diagnosis and not the measurement of severity, which is a distinct advantage that the AAST grading system offers (23,26). An operative severity classification like the AAST grading system is a more accurate and meaningful method to direct disease specific research and interventions rather than simple binary approach of simple versus complicated disease.…”
Section: Discussionmentioning
confidence: 99%